Riding the Wave of Trade: The Rise of Labor Regulation in the Golden Age of Globalization - Huberman, Michael; Meissner, Christopher M. (The Journal of Economic History, 2010)
The received view pins the adoption of labor regulation before 1914 on domestic forces. Using directed dyad-year event history analysis, we find that trade was also a pathway of diffusion. Market access served as an important instrument to encourage the diffusion of labor regulation. The type of trade mattered as much as the volume. In the European core, states emulated the labor regulation of partners because intra-industry trade was important. The New World exported less differentiated products and pressures to imitate were weak.